Perubahan Perilaku Tokoh Utama dalam Novel Seperti Dendam Rindu Harus Dibayar Tuntas karya Eka Kurniawan: : Kajian Psikologi Behaviorisme B. F. Skinner - Nugraha, Anggra; Hayati, Yenni (Persona: Kajian Bahasa dan Sastra, 2024)
This study aims to determine the form of changes in the main character's behavior in the novel Seperti Dendam Rindu Harus Dibayar Tuntas by Eka Kurniawan, the stimulus received by the main character in the novel Seperti Dendam Rindu Harus Dibayar Tuntas by Eka Kurniawan and the main character's response to the stimulus. This research uses literary psychology theory and is a qualitative research that uses descriptive method. Eka Kurniawan's novel entitled Seperti Dendam Rindu Harus Dibayar Tuntas is used as the data source for this research. The data collection methods include reading and understanding Eka Kurniawan's novel, finding and recording the main and additional characters in the novel, identifying events related to changes in the main character's behavior, and collecting data on changes in the main character's behavior. The validation technique used in this research is triangulation technique. The data analysis technique in this research is classifying the data based on the speech/actions or thoughts of the characters and narrators related to the form of behavior change, stimulus and response of the main character, analyzing/interpreting the data, formulating the results of data analysis, and writing a report. The results of this study are; (1) forms of changes in the main character's behavior. forms of behavior change are grouped into two parts namely; (a) natural changes, and (b) planned changes, (2) Stimuli obtained by the main character are grouped into two parts namely (a) Unconditioned stimulus and (b) Conditioned stimulus. and (3) The main character's response to the stimulus he received is grouped into two parts namely; (a) Unconditioned Response and (b) Conditioned Response.